Carex extensa Gooden. (Cyperaceae) en saladares continentales de montaña del Sistema Ibérico (provincia de Guadalajara, España) - Morales-Molino, César; Martínez-Sagarra, Gloria (Acta Botanica Malacitana, 2015)
.